Understanding the Role and Value of Librarians: A Study of Faculty Perceptions in Bayelsa State Universities, Nigeria - Ogunbodede, Kolawole Francis; Aborisade, Mariam Oyinda (International Journal of Knowledge Content Development & Technology, 2025)
The study examined faculty perceptions of librarians’ roles and values in Bayelsa State universities, Nigeria. The study’s population consisted of all faculty from three state universities in Bayelsa State. The sample size of 384 was adapted based on the method proposed by Fox et al. (2007) and Meyer (1979) for sampling from an infinite population due to the lack of an exact number of faculty members in the universities. An online survey was used to collect data, and 217 faculty responded to the online questionnaire. The data were analyzed using SPSS version 29. Findings revealed that faculty had a high level of interaction with librarians and were involved in a variety of interactions in various areas. Faculty have a high level of knowledge of librarians’ skills and duties, as well as a positive perception of librarians’ value. Therefore, university library administrations should purposefully encourage and facilitate frequent interactions between faculty and librarians to enhance their understanding of librarians’ expertise and roles, including collaboration through joint research and co-teaching opportunities.